2016
DOI: 10.1016/j.jfluidstructs.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a coupled floating offshore wind turbine analysis with high-fidelity methods

Abstract: This paper presents results of numerical computations for floating off-shore wind turbines using, as an example, a machine of 10-MW rated power. The aerodynamic loads on the rotor are computed using the Helicopter Multi-Block flow solver developed at the University of Liverpool. The method solves the Navier-Stokes equations in integral form using the arbitrary LagrangianEulerian formulation for time-dependent domains with moving boundaries. Hydrodynamic loads on the support platform are computed using the Smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…On the other hand, impacts of platform motions induced by waves and current on wind turbine aerodynamics have been investigated extensively using CFD methods either by imposing prescribed periodic motions to wind turbines [19][20][21][22] or via performing fully coupled aero-hydrodynamic analysis. [23][24][25] These CFD studies demonstrated that platform motions greatly affected wind turbine aerodynamics as well as its wake. However, they only focused on wind turbines with rigid blades.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, impacts of platform motions induced by waves and current on wind turbine aerodynamics have been investigated extensively using CFD methods either by imposing prescribed periodic motions to wind turbines [19][20][21][22] or via performing fully coupled aero-hydrodynamic analysis. [23][24][25] These CFD studies demonstrated that platform motions greatly affected wind turbine aerodynamics as well as its wake. However, they only focused on wind turbines with rigid blades.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, these studies are limited to fixed‐bottom wind turbines without considering platform motions in FOWT applications. On the other hand, impacts of platform motions induced by waves and current on wind turbine aerodynamics have been investigated extensively using CFD methods either by imposing prescribed periodic motions to wind turbines or via performing fully coupled aero‐hydrodynamic analysis . These CFD studies demonstrated that platform motions greatly affected wind turbine aerodynamics as well as its wake.…”
Section: Introductionmentioning
confidence: 99%
“…The MBDM was validated using simple mechanical systems of known solution as presented in Leble and Barakos (2016) like 2D and 3D slider-crank mechanisms. The gyroscopic wheel mechanism was used to validate that the gyroscopic effect is properly accounted for in the multi-body formulation.…”
Section: Validation Of Multi-body Dynamics Solvermentioning
confidence: 99%
“…FOWT model consists of three mooring lines and two rigid bodies: the rotor (blue) and combined body representing nacelle, tower and support (red). Adapted from Leble and Barakos (2016) that design, the present support is simplified to be symmetric with respect to the location of the tower and the floats are connected to the base of the tower with a solid frame. The size of the tower is taken from Bak et al (2013), and the dimensions of the support were calculated to provide sufficient buoyancy.…”
Section: Test Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation